Rethinking Camelot : JFK, The Vietnam War, and U.S. Political Culture - Chomsky, Noam (London Pluto Press, 2015)
Analyses the Kennedy Administration and draws controversial parallels between the Presidency of JFK and that of Ronald Reagan.
Include Index and Bibliography
Keywords: United States -- Vietnam War (1961-1975) -- Politics and government